A simple ion implanter for material modifications in agriculture and gemmology - S. Singkarat (2018)
© 2015 Elsevier B.V. In our efforts in developing ion beam technology for novel applications in biology and gemmology, an economic simple compact ion implanter especially for the purpose was constructed. The designing of the machine was aimed at providing our users with a simple, economic, user friendly, convenient and easily operateable ion implanter for ion implantation of biological living materials and gemstones for biotechnological applications and modification of gemstones, which would eventually contribute to the national agriculture, biomedicine and gem-industry developments. The machine was in a vertical setup so that the samples could be placed horizontally and even without fixing; in a non-mass-analyzing ion implanter style using mixed molecular and atomic nitrogen (N) ions so that material modifications could be more effective; equipped with a focusing/defocusing lens and an X-Y beam scanner so that a broad beam could be possible; and also equipped with a relatively small target chamber so that living biological samples could survive from the vacuum period during ion implantation. To save equipment materials and costs, most of the components of the machine were taken from decommissioned ion beam facilities. The maximum accelerating voltage of the accelerator was 100 kV, ideally necessary for crop mutation induction and gem modification by ion beams from our experience. N-ion implantation of local rice seeds and cut gemstones was carried out. Various phenotype changes of grown rice from the ion-implanted seeds and improvements in gemmological quality of the ion-bombarded gemstones were observed. The success in development of such a low-cost and simple-structured ion implanter provides developing countries with a model of utilizing our limited resources to develop novel accelerator-based technologies and applications.